2020
DOI: 10.3390/su12187613
|View full text |Cite
|
Sign up to set email alerts
|

How Circular Are the European Economies? A Taxonomic Analysis Based on the INEC (Index of National Economies’ Circularity)

Abstract: In this paper, the aggregate index of national economies’ circularity (INEC) was proposed and empirically verified. For this purpose, the taxonomic linear ordering method was used, which is a multi-criteria decision-making procedure. This method replaces the analysis of the phenomenon described by a set of indicators with an analysis using one aggregate indicator: the so-called ‘synthetic metric’. Based on 14 circular economy indicators that are available in the Eurostat database, the circularity indexes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Methods of constructing synthetic measures are the subject of numerous publications [41,[43][44][45]. Based on these foundations, the AEI index was designed by using the following procedure [40,44]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods of constructing synthetic measures are the subject of numerous publications [41,[43][44][45]. Based on these foundations, the AEI index was designed by using the following procedure [40,44]:…”
Section: Methodsmentioning
confidence: 99%
“…When constructing the synthetic index (AEI), the linear ordering method with the median and standard deviation was applied. Thanks to this, this method is characterized by a high resistance to the occurrence of extreme observations, which is particularly important from the point of view of comparative analysis of the EU countries [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…It is not only economic criteria that are important in this process. Ethics, morality, social responsibility, and, more recently, sustainable development are factors that can shape the decision-making process [16,80].…”
Section: Manager As a Decision-makermentioning
confidence: 99%
“…However, there is also a research gap identified in the literature [11][12][13], related to the cause-and-effect relations between decisions and organization culture. In the scientific literature, there is an awareness of strategy execution barriers in the decision-making process [14,15], and growing attention has been paid to organizations' strategies related to ecological aspects [16,17]. The scientific literature's dominant view presents the management styles as metaphors [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Saidani et al [11] identified 55 different sets of circularity indicators. Similarly, Kasztelan [12] developed and verified an empirically aggregated circular index of national economies (INEC), which uses 14 different indicators of circularity. That author estimated that the INEC value for 24 EU countries averages 0.3021, which, given that it can range from 0 to 1, indicates the low level of circularity that has been achieved in Europe.…”
Section: Introductionmentioning
confidence: 99%